Determinants of Environmental Disclosure in Indonesia - KISWANTO, KISWANTO; APRIYANI, Ika Diah; YANTO, Heri; HAJAWIYAH, Ain; DJAJADIKERTA, Hadrian Geri (Journal of Environmental Management and Tourism, 2020)
This study aims to identify the impacts of audit committees, audit committee meetings, and boards of commissioner meetings (BCM) on environmental performance and environmental disclosure (ED). The population of this study was 89 companies listed in LQ45 for the period 2011-2016. By using purposive sampling technique, this study identified 23 companies as samples. Path analysis based on the structural equation model was used. Environmental performance had a significant and positive effect on ED, audit committee meetings also determined ED and BCM, but have no effect on environmental performance. BCM did not have any significant effect on environmental performance. Audit committee had a significant positive effect on audit committee meetings. While size had a positive effect on the audit committee and BCM but did not affect the audit committee meeting. These results indicate that the discussion in audit committee meetings and BCM focused more on the ED rather than environmental performance.